The Impact of Microfinance Institution on Development of Small and Medium Enterprises: A Case Study of Lagos State - Bagudu, Hauwa Daniyan; Khan, Shazida Jan Mohd; Roslan, Abdul Hakim (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
The major target of this study is to evaluate the effect of Microfinance Institution (MFIs) on the development of SMEs (Small and medium enterprises) in Lagos state Nigeria. Simple random techniques of sampling were employed in this study in selecting 70 SMEs which constituted the size of the sample of the research. To facilitate the obtaining of relevant data that was used for analysis in this study, structured questionnaire was designed. Descriptive statistics involving simple graphical charts and tables was strategically applied in presentation and analysis of data. The outcome of the findings indicates that large number of SMEs are benefiting from the loans granted by the MFIs, despite the fact that few of them have sufficient ability to secure the needed amount. Interestingly, most of the SMEs admit positive MFIs loans contribution towards advancing their market share, the economic competitive advantage of the company and achieving market excellence through product innovation.